Cognitive functional approach to manage low back pain in male adolescent rowers: a randomised controlled trial. Issue 17 (24th January 2015) - Ng, Leo; Cañeiro, J P; Campbell, Amity; Smith, Anne; Burnett, Angus; O'Sullivan, Peter
Abstract : Background: Low back pain (LBP) is prevalent among adolescent rowers. This study evaluated the efficacy of a cognitive functional approach to reduce LBP in this population. Methods: Thirty-six adolescent male rowers reporting LBP participated. Nineteen were randomly allocated to the intervention group to receive a cognitive functional approach targeting cognitions, movement patterns, conditioning and lifestyle factors relevant to each rower for 8 weeks. The active control group (n=17) received usual care from their coaches (rowing skills and conditioning exercises). The primary outcome of the study was pain intensity as measured by the Numeric Pain Rating Scale during a 15 min ergometer trial preintervention and postintervention. Disability (Patient Specific Functional Scale and Roland Morris Disability Questionnaire) was measured preintervention/postintervention and at 12 weeks follow-up. Isometric muscle endurance of the back extensors and lower limb muscles, usual sitting posture and regional lumbar kinematic data during a 15 min ergometer row were measured preintervention/postintervention. Results: Compared with the control group, the intervention group reported significantly less pain during ergometer rowing (Numeric Pain Rating Scale −2.4, p=0.008) and reduced disability (Patient Specific Functional Scale (4.1, p=0.01); Roland Morris Disability Questionnaire (−1.7, p=0.003)) following the intervention, and at 12 weeks follow-up. They also demonstrated greater lower limb muscle endurance (20.9 s, p=0.03) and postured their lower lumbar spine in greater extension during static sitting (−9.6°, p=0.007). No significant differences were reported in back muscle endurance and regional lumbar kinematics during ergometer rowing. Conclusion: Cognitive functional approach was more effective than usual care in reducing pain and disability in adolescent male rowers. Clinical Trial Registry Number: Australian and New Zealand Clinical Trial Registry Number 12609000565246.